Structural and Vibrational Investigations and Molecular Docking Studies of a Vinca Alkoloid, Vinorelbine - Çelik, Sefa; AKYÜZ, SEVİM; Özel, Ayşen E. (Taylor & Francis Inc., 2022)
Vinorelbine, a vinca alkaloid, is an antimitotic drug that inhibits polymerisation process of tubulins to microtubules, and is widely used in cancer chemotherapy. Due to the importance of the structure-activity relationship, in this work the conformational preferences of the vinorelbine molecule were surched by PM3 method. The obtained lowest energy conformer was then optimized at DFT/B3LYP/6-31G(d,p) level of theory and the structural characteristics were determined. Frontier orbital (HOMO, LUMO) and molecular electrostatic potential (MEP) analyses were performed for the optimized structure. The experimental FT-IR, Raman and UV-VIS spectral data of vinorelbine along with the theoretical DFT/B3LYP/6-31G(d,p) calculations were investigated in detail. The vibrational wavenumbers were assigned based on the calculated potential energy distribution (PED) of the vibrational modes. To shed light into the anticancer property of vinorelbine as microtubule destabilizer, the most favourable binding mode and the interaction details between vinorelbine and tubulin were revealed by molecular docking studies of vinorelbine into the alpha,beta-tubulin (PDB IDs: 4O2B; 1SA0; 7CNN) and binding free energies were calculated by the combination of Molecular Mechanics/Generalized Born Surface Area (MMGBSA) and Molecular Mechanics/Poisson-Boltzmann Surface Area (MM-PBSA) methods {MM/PB(GB)SA}. The calculated vinorelbine-7CNN binding free energy, using by MM/PB(GB)SA approach, was found to be the best (-50.39 kcal/mol), and followed by vinorelbine-4O2B (-28.5 kcal/mol) and vinorelbine-1SA0 (-17.59 kcal/mol) systems. Moreover, the interaction of vinorelbine with the cytochrome P450 enzymes (CYP), which are known to help in the metabolism of many drugs in the body, was investigated by docking studies against CYP2D6 and CYP3A4 targets. Communicated by Ramaswamy H. Sarma
Keywords: Vinorelbine; Density Functional Theory; Molecular Docking; T-IR and Raman